Neuroscience : from the molecular to the cognitive - Bloom, Floyd E (Elsevier, 1994)
Neuroscientists and researchers in Alzheimer\'s disease will find this book essential reading.
Progress in brain research ; Vol. 100
Keywords: neurovědy